Qualitative nursing research: evidence of scientific validation from a translational perspective - Cruz Neto, João; de Oliveira Lima, Ainoã; Chaves Costa, Edmara (Investigación y Educación en Enfermería, 2024)
This article aims to reflect on scientific validation strategies in qualitative research in the light of translational theory in nursing. It is a reflection based on translational theory applied to nursing in strategies for validating qualitative studies. From this angle, validation is recognized as an adaptable construct, capable of eliciting/favoring an understanding of the subjectivity of the target audience in its relationship with the object of interest/study/research. The potential for advancing the science-profession lies in the interdisciplinary confluence of validation mechanisms, qualitative studies, the translational perspective, and nursing research. This confluence has the capacity to extend beyond theoretical and epistemological aspects. However, it is crucial to emphasize its profound, expressive, and relevant impact on the construction of scientific evidence. This impact aims to enhance the rigor and reliability of qualitative research, thereby bolstering its credibility and applicability in clinical practice.